2013
DOI: 10.1017/s1755773913000179
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges across political divides: experiments on deliberative democracy in deeply divided Belgium

Abstract: In recent years, deliberative democracy has moved from a philosophical ideal into an empirical theory with numerous experiments testing the theoretical assumptions. Despite the wealth of evidence on the potential for deliberation, scholars have remained hesitant to test the theoretical premises under rather more adverse circumstances. This article, in contrast, tries to push deliberative scholarship to its edge by focusing on the viability of citizen deliberation in deeply divided societies. Our research quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…Crucial determinants of the quality of participation are therefore the style of moderation (active involvement of the moderator can increase equal participation), the setting (hot deliberative settings are more confrontational than cold ones and therefore scare more people off), the size of the groups (large and diverse groups are more difficult to manage and have exclusionary tendencies) and other inhibiting factors such as the use of multiple languages (Caluwaerts and Deschouwer, 2013;Caluwaerts and Reuchamps, 2014).…”
Section: Quality Of Participationmentioning
confidence: 99%
“…Crucial determinants of the quality of participation are therefore the style of moderation (active involvement of the moderator can increase equal participation), the setting (hot deliberative settings are more confrontational than cold ones and therefore scare more people off), the size of the groups (large and diverse groups are more difficult to manage and have exclusionary tendencies) and other inhibiting factors such as the use of multiple languages (Caluwaerts and Deschouwer, 2013;Caluwaerts and Reuchamps, 2014).…”
Section: Quality Of Participationmentioning
confidence: 99%
“…In their analysis, the so‐called do‐democracy is rather a disguise for top‐down management of responsibilities in care. In addition to do‐democracy, welfare reforms were accompanied by experiments with ‘deliberative democracy’, in which random or focused selections of citizens are invited to deliberate about public issues . Scholars like Fraser and Polletta, however, point out that the specific types of discourse in deliberative democracy may also exclude the experiences and perspectives of people in marginal positions who have other ways of expressing themselves and have difficulties convincing other ‘deliberators’ .…”
Section: Discussionmentioning
confidence: 99%
“…Other experiments with democratic renewal during welfare reforms worked with deliberative forms of democracy. In ‘citizen summits’ or ‘mini publics’, citizens were selected based on random or purposeful selection and invited to deliberate about public issues . In well‐organized conversational settings supporting respect and listening, citizens deliberate and may form and alter their opinions without the pressures of the media and electorate faced by elected representatives.…”
Section: Introductionmentioning
confidence: 99%
“…This is the so-called 'contact hypothesis' in ethnic relations: 'intergroup contact tends to produce better intergroup attitudes and relations' (Amir, 1969: 319). Political psychologists have furthermore demonstrated that moderation appears on high stake issues through a better inclusion of arguments and views in heterogeneous rather than in homogeneous groups (Caluwaerts and Deschouwer, 2014;Caluwaerts and Reuchamps, 2014b). In the former case, individuals are more open and respectful towards other's views.…”
Section: Inter-community Contacts (H4)mentioning
confidence: 99%